PENGARUH STRATEGI PROMOSI DAN HARGA TERHADAP VOLUME PENJUALAN ALAT-ALAT KESEHATAN (HOSPITAL BED) PADA PT SARANDI KARYA NUGRAHA - Eka Patra (Universitas Pakuan, 2018)
The problems which is lifted in this research is how effect of promotion strategy and price on the salevolume either through by each other and also by together at PT. Sarandi Karya Nugraha. The purpose ofthis research is to know how big influence of promotion strategy and price either through by each otherand also together to raising of sale volume. Method data collecting used in this research is by distributedquestioner to customers in this case is the distributor of PT. Sarandi Karya Nugraha concerning theirperception about promotion strategy and price that is applied by the company. Later, Then the questioneris correlation with the level growth of volume sale of company bed hospital during period of year 2003-2006. Based on to result of examination with analysis of product moment by partial, known that there bestrong relationship between independent variable of promotion with dependent variable sale volume. Whilefor independent variable of price have relationship which enough strength (medium) to raising of salevolume. But by together the relationship both of the independent variable have strong relationship and givecontribution which high enough to raising the sale volume that is equal to 50,1%.